Response surface optimisation for acetone-butanol-ethanol production from cassava starch by co-culture of Clostridium butylicum and Bacillus subtilis - Benjamas Cheirsilp (Maejo International Journal of Science and Technology, 2011)
Acetone-butanol-ethanol (ABE) production from cassava starch was enhanced by a syntrophic co-culture of Clostridium butylicum TISTR 1032 and high amylase producing Bacillus subtilis WD 161 without anaerobic pretreatment. The production of amylase and ABE using this co-culture were respectively 16 and 6 times higher than those using the pure culture of C. butylicum TISTR 1032. The effect of the medium components on the performance of the co-culture was investigated using response surface methodology (RSM). Among the investigated components, cassava starch and ammonium nitrate contributed a significant effect on the production of amylase and ABE, while yeast extract had less effect. Based on the optimum strategy using RSM, the ABE production by the co-culture was improved 2.2-fold compared with that obtained from the initial condition and with a minimum requirement of nitrogen source.